ASSESSMENT AND TAXATION OF REAL ESTATE SALES (EXCHANGE) TRANSACTIONS - Nesterenko, Г. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2023)
When purchasing real estate in Ukraine, experts should evaluate the property. Taxation of such transactions is approved by Article 172 of the Tax Code of Ukraine. On August 23, 2023, the Notary Chamber of Ukraine validated the main principles of the procedure of charging personal income tax for sales (exchange) operations with real estate. Registration of the right to real estate always requires a great number and amount of obligatory payments. Everyone, who wants to exchange, sell, or present real estate or plans to inherit some property is interested in how much he/she should pay for the registration. Taxes and charges for such operations depend on some factors. The present work explains the peculiarities of that procedure. Expert evaluation of property is the procedure to determine the value of real estate when completing contracts of purchase and sale/rent/mortgage, etc. Expert evaluation of property is an obligatory document when registering a change of property ownership and is required for a correct amount of property tax to be determined. Services of evaluation companies are rather inexpensive and the corresponding information can be found on the company website (companies are randomly chosen from different regions of the country, table 1). All participants in the market are interested to maximum reduce the property value and, therefore, to pay less taxes. Nevertheless, it is technically impossible to significantly cut down the evaluation amount. According to the new rules of real estate evaluation, the estimated price varies within 25% of the so-called “registered price”, which is defined by the special national “assessment module” on the website of the State Property Fund of Ukraine. The Single database of property valuation reports (hereafter – the Single database) is the national automated information and telecommunication system that includes the database, software, module of online computation of the assessed price, service of online determination, and automatic generation of electronic certificates about the assessed prices of real estate objects. As of August 01, 2023, taxation of the real estate sales (exchange) transactions was validated by the Notary Chamber of Ukraine with consideration of the current version of the Tax Code, as well as the information available at the General information and reference resources of the State Tax Service (table 2). The number of sales is computed per year for each category of property with consideration of some peculiarities, particularly the sales of inherited property is computed separately (as a total for 1 and 3 entries) for each kind of object. Personal income tax (PIT) and military fee are paid by the seller, state duty – on agreement between the seller and buyer, whilst the buyer pays the Pension Fund fee. Parties of the transaction agree on who makes what payments. However, the payments should be done on behalf of the above-mentioned parties that are approved by the law (table 3). The tax is paid referring to the amount of profit gained from the sales. The profit is assessed according to the price mentioned in the contract of purchase and sale, i.e. from the amount which the buyer pays to the seller for the real estate object, but not less than the assessed price.